2003
DOI: 10.1007/s00066-003-1100-6
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Outcome and Prognostic Factors in the Radiotherapy of Recurrences of Cervical Carcinoma Following Surgery

Abstract: The probability of controlling recurrence mostly depends on a small tumor burden with the possibility of brachytherapy and/or complete surgery. Aggressive treatment modalities like radiochemotherapy and/or higher radiation doses are needed, especially for recurrences with infiltration of the pelvic wall and/or with macroscopic tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 35 publications
1
21
0
1
Order By: Relevance
“…[86][87][88]90,92 In Hille et al, 86 grade 3 late toxicity was observed in 8% of patients, including intestinal bleeding after 7 months and fistulae between the rectosigmoid colon and the vagina, removed subsequently by surgery. In Ito et al, 87 late complications of radiotherapy, including intestinal and urinary complications of grade 2 and grade 3, occurred in 32% of patients.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…[86][87][88]90,92 In Hille et al, 86 grade 3 late toxicity was observed in 8% of patients, including intestinal bleeding after 7 months and fistulae between the rectosigmoid colon and the vagina, removed subsequently by surgery. In Ito et al, 87 late complications of radiotherapy, including intestinal and urinary complications of grade 2 and grade 3, occurred in 32% of patients.…”
Section: Resultsmentioning
confidence: 98%
“…The interventions are radiotherapy or radiotherapy with chemotherapy (chemoradiotherapy). The search for relevant studies did not identify any RCTs but 16 case series met the inclusion criteria: nine evaluated radiotherapy [84][85][86][87][88][89][90][91][92] and seven evaluated chemoradiotherapy. [93][94][95][96][97][98][99] The results of the quality assessment for the radiotherapy and chemoradiotherapy studies are presented in Appendix 15.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations